Slip Deficit Rate and Seismic Potential on Crustal Faults in Tibet - Yanchuan Li; Xinjian Shan; Chunyan Qu; Guohong Zhang; Xuening Wang; Haicheng Xiong (Geophysical Research Letters)
Abstract Quantifying slip deficit rates on active faults in Tibet is essential for understanding fault kinematics and assessing seismic hazards, but has not been fully characterized, particularly on secondary faults. In this study, we integrate an updated interseismic Global Navigation Satellite Systems velocity field from 4,458 stations across continental China and its surroundings to calculate surface strain rates in Tibet, which we then use to invert for slip deficit rates on 263 crustal faults (383 segments). Our results reveal that ∼73% of strain rates are due to elastic strain accumulation on fault planes, and only a portion of the remaining strain rates may originate from unmodeled fault deformation. Quantitative calculations of seismic moment budgets on these fault segments indicate that they can produce earthquakes ranging from Mw 5.8 to 8.6, with 43 segments capable of generating earthquakes of Mw ≥ 7.5. Our findings provide a foundation for probabilistic seismic hazard analysis in Tibet.